Self-gated free-breathing 3D coronary CINE imaging with simultaneous water and fat visualization. - Jing Liu (PLoS ONE, 2014)
The aim of this study was to develop a novel technique for acquiring 3-dimensional (3D) coronary CINE magnetic resonance images with both water and fat visualization during free breathing and without external respiratory or cardiac gating. The implemented multi-echo hybrid 3D radial balanced Steady-State Free Precession (SSFP) sequence has an efficient data acquisition and is robust against motion. The k-space center along the slice encoding direction was repeatedly acquired to derive both respiratory and cardiac self-gating signals without an increase in scan time, enabling a free-breathing acquisition. The multi-echo acquisition allowed image reconstruction with water-fat separation, providing improved visualization of the coronary artery lumen. Ten healthy subjects were imaged successfully at 1.5 T, achieving a spatial resolution of 1.0 × 1.0 × 3.0 mm(3) and scan time of about 5 minutes. The proposed imaging technique provided coronary vessel depiction comparable to that obtained with conventional breath-hold imaging and navigator gated free-breathing imaging.